Acute rhabdomyolysis associated with atypical Guillain-Barré syndrome. Issue 783 (January 1991) - Scott, A. J.; Duncan, R.; Henderson, L.; Jamal, G. A.; Kennedy, P. G.
Abstract : We report a patient with atypical Guillain-Barré syndrome associated with acute rhabdomyolysis. Rhabdomyolysis may be the cause of elevation of creatine kinase sometimes seen in patients with Guillain-Barré syndrome.